2023
DOI: 10.1002/anie.202300726
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Assembly Modification of Homochiral Titanium–Organic Cages for Recognition and Separation of Molecular Isomers

Abstract: A chiral metal-organic cage (MOC) was extended and fixed into a porous framework using a post-assembly modification strategy, which made it easier to study the host-guest chemistry of the solidstate MOC using a single-crystal diffraction technique. Anionic Ti 4 L 6 (L = embonate) cage can be used as a 4connecting crystal engineering tecton, and its optical resolution was achieved, thus homochiral ΔΔΔΔ-and ΛΛΛΛ-[Ti 4 L 6 ] cages were obtained. Accordingly, a pair of homochiral cage-based microporous frameworks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…In order to visually observe the internal morphology of one-dimensional pores, we used Mercury 46 to simulate their pore structure using the contact surface method (Figures S39−S42). 47 Notably, [AlOC-199-L]•O n Pr can be scaled up for synthesis at the gram level (a single experiment can obtain 2.1 g of sample), which provides a foundation for subsequent performance exploration and practical application research (Figure 3a). The air stability, solvent stability, and thermal stability are confirmed by powder X-ray diffraction (PXRD) patterns of their bulk samples (Figures 3b and S43−S45).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to visually observe the internal morphology of one-dimensional pores, we used Mercury 46 to simulate their pore structure using the contact surface method (Figures S39−S42). 47 Notably, [AlOC-199-L]•O n Pr can be scaled up for synthesis at the gram level (a single experiment can obtain 2.1 g of sample), which provides a foundation for subsequent performance exploration and practical application research (Figure 3a). The air stability, solvent stability, and thermal stability are confirmed by powder X-ray diffraction (PXRD) patterns of their bulk samples (Figures 3b and S43−S45).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Considering the chiral structural features and the existence of considerable pore channels, we attempted to use it for enantiomeric separation of racemic 1-phenethylalcohol (PEOH) and obtained enantiomeric excess resolutions of 10.1% for the S-configurations of PEOH, this also validates homochiral channels from another perspective (Figures S48 and S49). 47 Given the one-dimensional channels and the presence of counter-anions in its structure, we performed anion-exchange experiments. The result showed that it not only exchanges inorganic anions like MnO 4 − (Figure S50), but also adsorbs large organic dye molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A large number of researchers meet the requirements of organic catalysis by designing the SBUs and organic ligands of MOFs. 17−19 In recent years, titanium oxide clusters, 20 zirconium oxygen clusters, 21 polyoxometalates, 22 transition-metal oxygen clusters, 23,24 and rare-earth oxygen clusters 25 have been successively discovered. These clusters can be applied for various organic catalysis because they not only have multiple catalytic centers but also can effectively enrich substrates as nanoreactors 26−28 to improve the catalytic performance through the confinement effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These characteristics facilitate the study of the PTC-236 in host-guest chemistry via single-crystal-to-single-crystal (SC-SC) transformation. Gratifyingly, PTC-236 was successfully utilized for the X-ray diffraction analyses of more than 20 guests, [11] including benzene (PhH) and its derivatives, aromatic/aliphatic nitriles, and aromatic alcohol molecules. Indeed, the hostguest interactions between the titanium cage and captured guests can be observed clearly.…”
Section: Introductionmentioning
confidence: 99%